A Circular Polarization Reconfigurable Antenna Based on Off‐Center‐Driven Dipoles. Issue 7 (9th July 2019) - Zhang, P.P.; Lin, G.Y.; Xiao, M.Z.; Cui, Y.H.
Abstract: A novel circular polarization (CP) reconfigurable antenna is proposed. The CP antenna consists of two folded off‐center‐driven dipoles. By switching four PIN diodes in the off‐center‐driven dipoles, the senses of CP can be changed between the left‐handed CP and the right‐handed CP. Two parasitic rectangular loops are added to the folded off‐center‐driven dipoles to improve the bandwidth. A T‐shaped microstrip probe line is used to feed the antenna. Experimental results show that the CP reconfigurable antenna achieves an impedance bandwidth of 31% (2.05–2.8 GHz) for return los >10 dB and a CP bandwidth of 16% (2.3–2.7 GHz) for axial ratio <3 dB. The measured gain of the CP reconfigurable antenna is about 7 dBi. Plain Language Summary: Polarization reconfigurable antenna technology has been proposed as a promising solution to the situation of crowded frequency spectrum nowadays. The polarization reconfigurable antenna can be reconfigured to feature more than one polarization characteristic in the same operation frequency; thus, frequency reuse is realized. Polarization reconfigurable antennas have been attracting lots of attention due to its unique features in enhancing the system capacity, increasing the transmission rate, and improving the stability and quality of communication. In this paper, a circular polarization reconfigurable antenna with a simple planar configuration is proposed, which may find wide applications in wireless and satellite systems. Key Points: A circular polarization reconfigurable antenna that consists of two folded off‐center‐driven dipoles is presented Operating principle and experimental results of the circular polarization reconfigurable antenna is discussed The CP reconfigurable antenna features a simple planar configuration and thus may find wide applications in wireless and satellite systems